Crack opening behavior in ceramic matrix composites. Issue 10 (14th June 2017) - Sevener, Kathleen M.; Tracy, Jared M.; Chen, Zhe; Kiser, James D.; Daly, Samantha
Abstract: The evolution of matrix cracks in a melt‐infiltrated SiC/SiC ceramic matrix composite (CMC) under uniaxial tension was examined using scanning electron microscopy (SEM) combined with digital image correlation (DIC) and manual crack opening displacement (COD) measurements. CMC modeling and life prediction strongly depend a thorough understanding of when matrix cracks occur, the extent of cracking for given conditions (time‐temperature‐environment‐stress), and the interactions of matrix cracks with fibers and interfaces. In this work, strain relaxation due to matrix cracking, the relationship between CODs and applied stress, and damage evolution at stresses below the proportional limit were assessed. Direct experimental observation of strain relaxation adjacent to regions of matrix cracking is presented and discussed. Additionally, crack openings were found to increase linearly with increasing applied stress, and no crack was found to pass fully through the gage cross‐section. This calls into question the modeling assumption of through‐cracks for all loading conditions and fiber architectures, which can obscure oxidation mechanisms that are active in realistic cracking conditions. Finally, the combination of SEM with DIC is demonstrated throughout to be a powerful means for damage identification and quantification in CMCs at stresses well below the proportional limit.